U.K. controlled trial of intrapleural streptokinase for pleural infection - Maskell, N; Davies, C; Nunn, A; Hedley, E; Gleeson, F; Miller, R; Gabe, R; Rees, G; Peto, T; Woodhead, M; Lane, D; Darbyshire, J; et al. (2005)
BACKGROUND: Intrapleural fibrinolytic agents are used in the drainage of infected pleural-fluid collections. This use is based on small trials that did not have the statistical power to evaluate accurately important clinical outcomes, including safety. We conducted a trial to clarify the therapeutic role of intrapleural streptokinase. METHODS: In this double-blind trial, 454 patients with pleural infection (defined by the presence of purulent pleural fluid or pleural fluid with a pH below 7.2 with signs of infection or by proven bacterial invasion of the pleural space) were randomly assigned to receive either intrapleural streptokinase (250,000 IU twice daily for three days) or placebo. Patients received antibiotics and underwent chest-tube drainage, surgery, and other treatment as part of routine care. The number of patients in the two groups who had died or needed surgical drainage at three months was compared (the primary end point); secondary end points were the rates of death and of surgery (analyzed separately), the radiographic outcome, and the length of the hospital stay. RESULTS: The groups were well matched at baseline. Among the 427 patients who received streptokinase or placebo, there was no significant difference between the groups in the proportion of patients who died or needed surgery (with streptokinase: 64 of 206 patients [31 percent]; with placebo: 60 of 221 [27 percent]; relative risk, 1.14 [95 percent confidence interval, 0.85 to 1.54; P=0.43), a result that excluded a clinically significant benefit of streptokinase. There was no benefit to streptokinase in terms of mortality, rate of surgery, radiographic outcomes, or length of the hospital stay. Serious adverse events (chest pain, fever, or allergy) were more common with streptokinase (7 percent, vs. 3 percent with placebo; relative risk, 2.49 [95 percent confidence interval, 0.98 to 6.36]; P=0.08). CONCLUSIONS: The intrapleural administration of streptokinase does not improve mortality, the rate of surgery, or the length of the hospital stay among patients with pleural infection. Copyright © 2005 Massachusetts Medical Society.